Characteristic Study on Malaysia Power Plant Fly Ash Cenosphere - Beddu S.; Zainoodin M.M.; Muda Z.C.; Mohamad D.; Mohamed Nazri F.; Itam Z.; Sadon S.N. (Springer, 2023)
Alumina; Aluminum oxide; Chemical industry; Concretes; Fly ash; Gas industry; Highway engineering; Particle size; Particle size analysis; Power plants; Silica; Surface morphology; Cenospheres; Characteristic; Characteristic properties; Chemical compositions; Crystallographic structure; Engineering industries; Oil and Gas Industry; Spherical morphologies; Morphology